HDAC2-dependent Antipsychotic-like Effects of Chronic Treatment with the HDAC Inhibitor SAHA in Mice. (15th September 2018) - de la Fuente Revenga, Mario; Ibi, Daisuke; Saunders, Justin M.; Cuddy, Travis; Ijaz, Maryum K.; Toneatti, Rudy; Kurita, Mitsumasa; Holloway, Terrell; Shen, Li; Seto, Jeremy; Dozmorov, Mikhail G.; González-Maeso, Javier
Highlights: Inhibition or genetic deletion of HDAC2 results in antipsychotic-like phenotypes. HDAC2 underlies the negative effects of chronic clozapine on cortical synapses. Chronic HDAC inhibition augments expression of plasticity-related genes. HDAC2 may represent a new epigenetic target for the treatment of schizophrenia. Abstract: Antipsychotic drugs, including both typical such as haloperidol and atypical such as clozapine, remain the current standard for schizophrenia treatment. These agents are relatively effective in treating hallucinations and delusions. However, cognitive deficits are at present essentially either persistent or exacerbated following chronic antipsychotic drug exposure. This underlines the need of new therapeutic approaches to improve cognition in treated schizophrenia patients. Our previous findings suggested that upregulation of histone deacetylase 2 (HDAC2) expression upon chronic antipsychotic treatment may lead to negative effects on cognition and cortical synaptic structure. Here we tested different phenotypes of psychosis, synaptic plasticity, cognition and antipsychotic drug action in HDAC2 conditional knockout ( HDAC2-cKO ) mice and controls. Conditional depletion of HDAC2 function in glutamatergic pyramidal neurons led to a protective phenotype against behavior models induced by psychedelic and dissociative drugs, such as DOI and MK801, respectively. Immunoreactivity toward synaptophysin, which labels presynaptic terminals of functional synapses, was decreased in the frontal cortex of control mice chronically treated with clozapine – an opposite effect occurred in HDAC2-cKO mice. Chronic treatment with the class I and class II HDAC inhibitor SAHA prevented via HDAC2 the disruptive effects of MK801 on recognition memory. Additionally, chronic SAHA treatment affected transcription of numerous plasticity-related genes in the frontal cortex of control mice, an effect that was not observed in HDAC2-cKO animals. Together, these findings suggest that HDAC2 may represent a novel target to improve synaptic plasticity and cognition in treated schizophrenia patients.